Feasibility of gabapentin as an intervention for neurorecovery after an acute spinal cord injury: Protocol - Wilson, James R.; Doty, Samuel; Petitt, Jordan C.; El-Abtah, Mohamed; Francis, John J.; Sharpe, Megan G.; Kelly, Michael L.; Anderson, Kim D. (Frontiers in Neurology, 2022)
Introduction This protocol is describing the first ever prospective, mock-efficacy, dose exploration trial design testing the feasibility of administering gabapentin in the acute setting as an intervention for neurorecovery. Gabapentin is an FDA-approved medication for treating seizures and postherpetic neuralgia and is used broadly off-label for neuropathic pain management for many conditions, including spinal cord injury. Emerging data suggests that when given early after spinal cord injury onset and in low-medium doses, gabapentin may have properties that promote recovery of neurological function. The objective of this trial is to assess the feasibility of conducting an efficacy trial in which gabapentin is started early after injury, is restricted in its dose, and is not used for pain management. Methods and analysis Forty-two people aged 18 years or older with any level and any severity of spinal cord injury induced by a trauma will be enrolled, randomized, and have the first dose of study medication by 120 h post-injury onset. Participants will be randomly assigned to one of three groups: 600, 1,800 mg/day gabapentin, or placebo. Study medication will be given for a 90-day duration. Blinded assessments will be obtained at 7 days post-injury (baseline), 30 days post-injury (interim), after the 90-day treatment duration/approximately 3 months post-injury (end of treatment), and at 6 months post-injury (end of study). The key analysis parameters will evaluate feasibility of recruitment of target population, delivery of drug treatment protocol, maintenance of blinding, and retention of participants. Discussion Outputs from this trial will inform research and clinical practice on the effects of manipulating gabapentin for non-pain management purposes in the acute setting and will guide the development of a properly powered efficacy trial of gabapentin as an intervention for neurorecovery in spinal cord injury. Ethics and dissemination The study was approved by the MetroHealth Institutional Review Board (IRB21-00609) and registered at clinicaltrials.gov prior to enrolling any participants. Dissemination will include peer-reviewed publications, presentations at professional conferences and in the community, and through other healthcare and public venues. Clinical trial registration www.ClinicalTrials.gov, identifier: NCT05302999; protocol version 1.1 approved 05/23/2022. Trial funding National Institute on Disability, Independent Living and Rehabilitation Research.